Characterization of Staphylococcus aureus Cardiolipin Synthases 1 and 2 and Their Contribution to Accumulation of Cardiolipin in Stationary Phase and within Phagocytes - Koprivnjak, T. (American Society for Microbiology, 2011)
In many bacteria, including Staphylococcus aureus, progression from the logarithmic to the stationary phase is accompanied by conversion of most of bacterial membrane phosphatidylglycerol (PG) to cardiolipin (CL). Phagocytosis of S. aureus by human neutrophils also induces the conversion of most bacterial PG to CL. The genome of all sequenced strains of S. aureus contains two open reading frames (ORFs) predicting proteins encoded with ∼30% identity to the principal CL synthase (cls) of Escherichia coli. To test whether these ORFs (cls1 and cls2) encode cardiolipin synthases and contribute to CL accumulation in S. aureus, we expressed these proteins in a cls strain of E. coli and created isogenic single and double mutants in S. aureus. The expression of either Cls1 or Cls2 in CL-deficient E. coli resulted in CL accumulation in the stationary phase. S. aureus with deletion of both cls1 and cls2 showed no detectable CL accumulation in the stationary phase or after phagocytosis by neutrophils. CL accumulation in the stationary phase was due almost solely to Cls2, whereas both Cls1 and Cls2 contributed to CL accumulation following phagocytosis by neutrophils. Differences in the relative contributions of Cls1 and Cls2 to CL accumulation under different triggering conditions suggest differences in the role and regulation of these two enzymes.